Pleasure and the good life: concerning the nature, varieties, and plausibility of hedonism - Feldeman, Fred (Fred Feldman, 2006)
"Clearly written, accessible...[the book contains an] acute, ingenious, and concise disposal of many objections to hedonism...valuable especially for its insightful discussion of many objections and alternatives to hedonism, from Plato to the present, and of Epicurus' attempts at its revision and Feldman's own."--Notre Dame Philosophical Reviews Product Description Since ancient times, hedonism has been one of the most attractive and controversial theories about "the Good Life." On this view, the Good Life is the pleasant life-- pleasure is the Good. Now Fred Feldman presents a careful, modern formulation of hedonism, defending the theory against some of the most important objections. Distinguishing some diverse variants of the theory, and assessing their merits, Feldman explains why each deserves to be classified as a form of hedonism. His book offers inspiring vindication for anyone who hopes that it is possible to enjoy oneself and be good at the same time.